PENGEMBANGAN MODUL MENULIS TEKS NARASI BERBASIS COOPERATIVE LEARNING UNTUK SISWA KELAS IV SEKOLAH DASAR - Subianto; Putri, Dwi Syah; Rezki Muhammad Akbar; Elyusra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a cooperative learning-based narrative writing module for fourth-grade elementary school students and to test the validity, practicality, and effectiveness of its use. This study employed the Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Research data were obtained through expert validation sheets, teacher and student response questionnaires, and narrative writing ability tests. Data analysis was conducted using both quantitative and qualitative descriptive methods to determine the feasibility of the developed product. The results showed that the developed module achieved a validity level of 94.83%, falling into the “highly valid” category. Teacher feedback on the module’s use was 93.33%, while student feedback was 88.20%, both falling into the “highly practical” category. The use of the module also demonstrated an improvement in students’ narrative writing skills, with the average score increasing from 67.40 on the pretest to 84.63 on the posttest, and an N-Gain value of 0.53, classified as “moderate.” This study shows that a cooperative learning-based narrative text writing module can serve as an innovative teaching resource that integrates content, the writing process, and collaborative interaction to support writing literacy learning in elementary schools.